Burden on caregivers of patients with sequelae of cerebrovascular accident - Tatiana Ferreira da Costa; Cláudia Jeane Lopes Pimenta; Maria Miriam Lima da Nóbrega; Maria das Graças Melo Fernandes; Inácia Sátiro Xavier de França; Maria de Lourdes de Farias Pontes; Kátia Neyla de Freitas Macedo Costa
ABSTRACT Objectives: to evaluate the burden and its relationship with the sociodemographic characteristics of caregivers of people with sequelae of stroke. Methods: a cross-sectional, exploratory, and quantitative study was conducted with 151 caregivers of people with sequelae of stroke, through home interviews between September and December 2017. Results: there was a general mean of low burden. The items that indicated the worst changes were: "My time for social activities with friends," "My time for family activities," "My ability to cope with stress," and "My physical functioning." There was an association of burden with the female sex and with caregivers who have been assisting for longer. Conclusions: the results allow us to reflect on the need to create a policy aimed at family caregivers to reduce the impact of care delivery.